Pengembangan Ekonomi Kreatif Produk Industri Rumah Tangga dan UMKM di Desa Pelehu Kecamatan Bilato Kabupaten Gorontalo - Sri Endang Saleh; Ismail Djakaria; Mentari Rizki Sawitri Pilomonu (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Business activities are mostly dominated by the community through the frame of Creative Economy and Micro, Small, and Menengan Enterprises. The choice of this frame is because the concept is simple and affordable, especially for the lower middle class. Home industry products in the framework of MSMEs play a major role in economic growth and employment. Problems for the creative economy and MSMEs include a lack of knowledge about the establishment of MSMEs, no permits, no branding, and the most important problem is digital marketing strategies. This is also found in Pelehu Village, Bilato District, with small household industries (MSMEs) starting to be developed but not yet using a digital business system, the appearance side of both Labeling, Packaging, and marketing is still relatively traditional and does not have a business license. To improve the economic self-sufficiency of business actors in Pelehu Village, Bilato District, Gorontalo Regency, the Thematic KKN implementation team by involving lecturers and students conducted socialization and training for MSME actors, housewives, and MSME observers. The main objectives of this Thematic KKN program are to assist MSMEs related to business licensing to obtain a Business Identification Number (BIN) to be legally legal; foster business actors to design MSME products and digital marketing systems; and involve students in guiding and motivating MSME actors. With the hope that it can independently encourage the economy in the Pelehu village area, Bilato District, Gorontalo Regency.